Analisis Framing Film Tuhan Izinkan Aku Berdosa - Kurnia Handita (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The film "Tuhan Izinkan Aku Berdosa" is an interesting work to be analyzed from the perspective of moral and religious framing. Hanung Bramantyo's film adaptation of Muhidin M. Dahlan's novel "Tuhan Izinkan Aku Menjadi Pelacur" offers a complex and controversial framing analysis. In this movie, themes of morality and religion are explored through a complex narrative and deep characters. The moral framing in the movie highlights the complex moral dilemma faced by the main character, who tries to balance between his religious faith and a complicated personal life. Religious framing in this context addresses the way the movie portrays religious teachings, religious practices, and their influence on the character's life. This research uses a descriptive qualitative method. George Lakoff's framing theory and framing theory in media studies provide a foundation for understanding how the selection of visual and narrative viewpoints can influence audience interpretation. The research is based on an in-depth literature study, including analysis of several related journals and books that discuss the role of framing in film. Through this approach, the movie "God Permits Me to Sin" is explained not only as a visual narrative, but also as a work of art that uses framing techniques to explore the psychological and social complexities in the story. .